Optimization of process factors for solid-state bioconversion of domestic wastewater sludge - Mollah, Md. Fazlul Awal; Fakhru’l-Razi, A.; Hanafi, M. Musa; Alam, Md. Zahangir (Elsevier Ltd., 2004)
Since optimization of operational parameters is the key factor for solid-state bioconversion (SSB) by microorganisms, the growth,proliferation and establishment of two compatible mixed fungal cultures, Trichoderma harzianum with Phanerochaete chrysosporium 2094 and T. harzianum with Mucor hiemalis were evaluated under di6erent operational parameters for conducting e7ciently the SSB of domestic wastewater sludge. Growth and development of selective mixed cultures were ascertained by evaluation of dry mycelial biomass, total organic carbon, soluble protein production and radial growth rate in growth media containing domestic wastewater sludge. A carbon:nitrogen (C:N) ratio of 30:1, a cheapand easily available carbon-rich co-substrate (wheat <our), an initial substrate pH of 4.5– 5.5 and presence of bulking material (rice straw) gave signi.cantly higher mycelial biomass, total organic carbon, soluble protein and growth rates than other treatments. These conditions may be e6ective for large-scale SSB of domestic wastewater sludge by these mixed fungal cultures